Strategi Pengelolaan Industri Kerajinan Keramik Borneo Lentera Prima Singkawang (FKIP, Universitas Palangka Raya, 2021)
The Borneo Lentera Prima ceramic handicraft industry is an industrial center that houses a group of craftsmen in the ceramic field in the Singkawang area. This industry is a production place for ceramic goods which is still active from several other industrial groups. This handicraft industry group can survive and develop itself. This is based on the existence of a management system that is well managed, so that it can maintain its existence in the industrial world, creatively and innovatively. The purpose of this research activity includes the concept of existence which is developed in the management of the Borneo Lentera Prima ceramic industry in Singkawang, by paying attention to worker management strategies, product forms and marketing strategies. The method used in this research is an interdisciplinary approach with a qualitative case study method, supported by several disciplines such as socio-culture, management. The data collection process was obtained from the field by means of observation, interviews, and related and relevant documents. The existence process carried out by the management of the Borneo Lentera Prima Singkawang ceramic craft industry includes an appropriate wage system, so that it can make every craftsman have an income according to economic needs. Other stages of existence include a distinctive form as a cultural identity, so that it has an appeal to the market, but in achieving success in sales management undertakes a marketing strategy that includes goals, needs, excellence and renewal.